EFFECTIVENESS OF ORGANIC FERTILIZERS IN INCREASING THE YIELD OF LOCAL SWEET POTATO VARIETIES IN ACIDIC DRYLANDS OF NORTH SUMATRA - Vivi aryati; Jonharnas; Yudhistira Nugraha; Novia Chairuman; Siti Fatimah Batubara; Evawaty Sri Ulina; Dorkas Parhusip; Imelda Marpaung; Idawanni; Siti Rosmanah; Yahumri; Abdul Azis (Gunung Djati Conference Series, 2026)
This study aims to evaluate the effectiveness of various organic fertilizers in increasing the yields of local sweet potato varieties in the acidic drylands of North Sumatra. The experiment was conducted using a systematic tillage method with 100 cm x 25 cm plant spacing. Organic fertilizers were applied at a dose of 5 t ha-1, supplemented with inorganic fertilizers (200 kg NPK and 150 kg Urea). Maintenance included three rounds of weeding, hilling, and vine turning, with harvesting conducted 3.5 months after planting. Farming analysis results revealed that goat manure (O1) yielded the highest average of 25,733 kg/ha, generating an income of IDR 60,372,000 ha-1 with a B/C ratio of 1.42. Rice husk compost (O2) followed with 24,821 kg ha-1 (B/C ratio 1.46), while oil palm empty fruit bunches (O3) and the control group without organic fertilizer (O4) produced lower yields of 16,487 kg ha-1 and 14,906 kg ha-1, respectively. Among the tested varieties, V3 achieved the highest average yield (20,740 kg ha1) compared to V2 (20,685 kg ha-1) and V1 (20,191 kg ha-1). The study concludes that the application of goat manure and rice husk compost significantly enhances sweet potato productivity in acidic drylands, increasing farmers' income by up to 91.27%. Furthermore, these organic amendments are recommended to improve soil structure in compacted acidic dryland areas.